Soil fauna: Bioindicator of soil recovery in Brazilian savannah - Giácomo, Rômulo Guimarães [UNESP]; De Souza, Rodrigo Camara; Alves, Marlene Cristina [UNESP]; Pereira, Marcos Gervasio; De Arruda, Otton Garcia; González, Antonio Paz (Revista Brasileira de Ciencias Agrarias, 2017)
This work aimed to evaluate the employment of the soil arthropod community as a bioindicator of land reclamation on a loan area in Mabea fistulifera Mart. plantation under different types of fertilization, in central-western Brazil. The experimental design was a randomized complete block design within plots (type of fertilization applied in the planting line). The quarterly sampling of the organisms occurred along two years, by means of pitfall traps, in six treatments (08 traps/treatment): area without intervention (SI); planting without fertilization (D0); planting with application of mineral fertilizer (DAM); three different doses of an organic compound (industrial residue) obtained from the pulp production, 10 Mg ha-1 (D10), 15 Mg ha-1 (D15), and 20 Mg ha-1 (D20). Each trap was considered a sample unit. The animals were identified in high taxonomic groups (order, class, family). There was no clear pattern of the effect of the treatments on the structure (total and average richness, uniformity, diversity, total abundance) of the community. However, the principal component analysis indicated that D20 increased the abundance of a higher number of taxonomic groups/trophic guilds, in comparison to the other treatments.
Keywords: Degraded area; Mabea fistulifera; Soil conditioning